Influência do laser de diodo na evaporação do solvente de sistemas adesivos e na variação de temperatura na câmara pulpar - Friedrich, Luciana Roggia (2013)
This study aimed to evaluate in vitro the influence of diode laser in solvent evaporation of adhesive systems and in the pulp chamber temperature variation. It was carried out in two stages: a) to evaluate the grade of solvent evaporation (GE) by the gravimetric method in which 10 μL of each of the tested materials, being two of them etch-and-rinse adhesive systems (Adper Scotchbond Multi Purpose, 3M ESPE and Adper Single Bond 2, 3M ESPE) and two self-etching adhesive systems (Clearfil SE Bond, Kuraray and Optibond All-in-one, Kerr), were put in a concave glass container and the mass loss was measured in a analytical digital balance, after the application of the following techniques of solvent evaporation: air dry stream kept a distance of 10 cm from the tooth surface for 5 seconds (control technique) and diode laser irradiated continuously, perpendicularly and 1 cm distant from the tooth surface, in power outputs 1, 2 and 3 W for 5, 10 15, 20 and 25 seconds (experimental techniques). For each one of the 4 adhesive systems and in each one of the 4 evaporation techniques assessed, six series of monitoring were taken (n=6); b) to assess the temperature alteration in which the ten inferior central incisive teeth were selected (n=10), that had their root canals extended and filled with thermal paste. Afterwards, the root portion was submerged in thermal bath at 37°C and the thermocouple sensor, attached to a digital thermometer, was set up inside the pulp chamber. The diode laser was applied in the vestibular of the tooth crown, at 1 cm of distant from the surface and at 2 mm from the cementoenamel junction, in the power outputs 1, 2 e 3 W in a continuous mode and for the times 5, 10, 15 and 25 seconds. For each power output and in each tooth, five records of temperature as well as the record of the initial temperature, were carried out. The data on solvent evaporation rate (GE) and on the temperature variation were subjected to variance analysis and Tukey s test (α= 5%). Based on the values obtained from GE, the power output of 3 W for 25 seconds was that caused higher evaporation of the solvent, being better than the air dry stream technique to the adhesive systems Adper Scotchbond Multi Purpose e Adper Single Bond 2, and similar to the systems Clearfill SE Bond e Optibond All-in-One. Althogh thee was a significant statistical difference among the laser power outputs which were used and in all time intervals, the power output of 3W was the one which resulted in the highest average variation in temperature (3,27 °C), followed by 2 W (2,30 °C) and by 1 W (1,08 °C). Thus, the diode laser caused the solvent evaporation being dependent of the inherent characteristics of each adhesive system and, the parameters of diode laser irradiation employed in the current study didn t cause any damage to the pulp tissue.